Analytical Solution of Time-Varying Investment Returns with Random Parameters - Osu, Bright O.; Amadi, I.U; Azor, P.A (Journal of Pure & Applied Sciences, 2022)
In this paper, a combination of deterministic and stochastic systems with its random parameters in the model was considered. The analytical solution to the proposed model is presented in detail which determined the following insurance quantities or variables such as: surplus process of insurance company, risky and risk-less assets. These results were explicitly verified graphically and the effects of the expected rate of return were discussed.